Finding Top-k Sequences over Data Streams according to Temporal Conditional Preferences - Ribeiro, Marcos Roberto; Barioni, Maria Camila N.; de Amo, Sandra; Roncancio, Claudia; Labbé, Cyril (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2018: Anais do XXXIII Simpósio Brasileiro de Banco de Dados, 2018)
Recently, several research works have been conducted on processing of preference queries over data streams. Preference queries are useful for many application domains where users aim to find out the closest data items to their wishes. This paper presents a new operator for the StreamPref language that can be employed to obtain the top-k data stream sequences according to temporal conditional preferences. Temporal conditional preferences can allow a user to express how past instants of a data stream may influence his preferences at a present instant. In order to evaluate this new operator, two new algorithm strategies are also presented. The extensive set of experiments performed show that the incremental strategy presents a superior performance in all experimental settings. Moreover, the results achieved show that the proposed operator has a superior performance when compared to the equivalent operation in CQL.